INVESTIGATING THE ROLE OF GREEN MARKETING IN CONSUMER DECISION-MAKING PROCESSES - Haryaman, Adang; Ayu Amrita, Nyoman Dwika (Yayasan Kreatif Indonesia Emas, 2025)
Background The growing awareness of environmental issues has prompted both businesses and consumers to adopt more sustainable practices. As a result, green marketing has emerged as a critical strategy for companies to not only showcase their commitment to sustainability but also cater to a market segment increasingly concerned with environmental preservation. The role of green marketing in shaping consumer decision-making processes has been a subject of interest, particularly regarding how various elements, such as trust in environmental claims, perceived environmental value, and consumer awareness, influence purchasing behavior. With the rise of greenwashing concerns and the need for businesses to differentiate themselves, understanding how consumers perceive and engage with green products is essential. Aims This study aims to explore the role of green marketing in shaping consumer decision-making. It specifically focuses on assessing consumer awareness of green marketing, investigating the influence of trust in environmental claims on purchasing behavior, examining the perceived environmental value of green products, and identifying factors that drive or hinder consumer engagement with such products. The goal is to provide actionable recommendations for businesses to improve their green marketing strategies and build consumer loyalty. Research Method A mixed-method approach was used, combining both quantitative and qualitative techniques. A survey was conducted across diverse demographics to gather data on consumer awareness, trust in environmental claims, and perceptions of green products. Interviews with a smaller group of respondents provided deeper insights into consumer attitudes and factors influencing their decisions. The data was analyzed using statistical methods and thematic analysis to uncover trends and consumer perceptions. Results and Conclusion The study found that consumer awareness of green marketing is high, especially among younger, more educated groups, though awareness varies across demographics. Trust in green marketing claims was critical, with consumers showing more trust in products with third-party certifications and clear impact reporting. Despite positive perceptions of green products' environmental value, challenges such as greenwashing and price sensitivity hinder broader engagement. The research concludes that businesses must prioritize authenticity, transparency, and education to effectively engage consumers and promote sustainable purchasing behavior. Contribution This research contributes valuable insights into how green marketing affects consumer decisions. It emphasizes the need for clear communication and consumer trust in effective green marketing strategies. The findings provide practical recommendations for businesses to enhance their environmental claims and foster loyalty, while also informing policymakers on how to encourage sustainable consumption patterns.